Effect of tillage and precision nutrient placement on below-ground biomass, nutrient content and yield of maize (Zea mays L.) - SONNAD, PRAKASH; SINGH, TEEKAM; RATHORE, S.S.; SINGH, RAJIV KUMAR; JAMAKHANDI, HUCHCHAPPA; RAWAT, SATYAM; BHOI, SOUMYA PRAKASH; SANDEEP (Journal of Soil and Water Conservation, 2026)
A comprehensive experiment was conducted at ICAR–Indian Agricultural Research Institute in New Delhi, during the Kharif season, 2022–2023 to assess effect of tillage and precision nutrient placement on below ground biomass and nutrient content of maize (Zea mays L.). Experiment was conducted in split plot design with 3 main plot treatments of different tillage viz., T1, (conventional tillage); T2, (once rotavator as minimum tillage) and T3, (zero tillage) and 4, precision nutrient application options N1, 50% RDF as point placement; N2, 75% RDF as band placement; N3, 100% RDF as band placement and N4, 100% RDF as broadcasting were tested in subplots and replicated thrice. Results revealed that minimum tillage as 49.50% fresh root weight (g plant-1), 102.7% root dry weight (g plant-1), 17.4% root length (cm), 24.2% root surface area (cm² cm-³), 46.49% root volume(cm3), 21.21% root mass density as compared to conventional tillage (T1) which is mainly due to crop residue incorporated in minimum tillage. The highest N, P and K content in maize grain and stover were recorded with minimum tillage, while the lowest content of all these nutrients was recorded with conventional tillage. The 100% RDF through band placement (N3) resulted 45.59% fresh root weight (g plant-1), 32.7% root dry weight (g plant-1), 21.72% root volume (cm3), 11.4% root length (cm), 20% root surface area (cm² cm-³), 20% root mass density compared to 100% RDF as broadcasting (N4). While 100% RDF of band placement yielded the maximum N, P, and K content in maize grains and stover, it was statistically equivalent to 50% RDF of point placement. Strong positive connections between maize grain yield, yield characteristics, and nutritional content are found in the study, underscoring their combined importance in raising productivity. The findings indicated that the adoption of minimum tillage coupled with precise point nutrient placement significantly enhanced below-ground biomass and nutrient accumulation in maize (Zea mays L.) during the kharif season, while enabling a 50% reduction in fertilizer use efficiency without compromising crop performance.